Proklamasi 17 agustus 1945: tonggak penegakan hak bangsa indonesia atas kemerdekaan - Sugiarti, Dwi (Maliki Interdisciplinary Journal, 2025)
The colonization of Indonesia began with the arrival of Europeans, especially the Portuguese and the Dutch, which led to the establishment of the VOC (Verenigde Oostindische Compagnie) in 1602. The VOC implemented a system of trade monopoly and forced labor that oppressed the Indonesian people. The Dutch also used military force to overcome the resistance that emerged, such as the Diponegoro War (1825-1830) and the Aceh War (1873-1904). In the 20th century, more organized national movements emerged, such as Budi Utomo, Sarekat Islam, and the Indonesian National Party (PNI), which played an important role in fighting for Indonesian independence. The Japanese occupation in 1942 also brought suffering to the Indonesian people, but also provided an opportunity to prepare for Indonesian independence through the establishment of the Investigating Agency for Preparatory Work for Indonesian Independence (BPUPKI). The Indonesian people’s resistance to colonialism has been going on for a long time and is an important part of the history of the nation’s struggle.